The Influence Of Dynamic Leadership And Time Management On Work Productivity With Intellectual Intelligence As Moderation - Damma Setiawan, Rorenso Rakhitta; Mutiara Dewi, Sintia (Fakultas Bisnis, 2024)
According to data from the Ministry of Manpower (Kemnaker), work productivity in Indonesia seen from the last five years has increased. In 2018, the number of work productivity in Indonesia reached Rp82.56 million in the following year, increasing and for 2020 it decreased due to the occurrence of Covid-19. In 2021, productivity began to rise and in 2022 it experienced an increase or record high for the last five years of IDR 86.55. If cumulative from 2018 – 2022, the work productivity figure increased by 4.8%. In addition, companies in Indonesia must also have the ability to interact effectively with employees in their work. This study aims to investigate the influence of dynamic leadership and time management on work productivity, as well as the impact of intellectual intelligence as a moderator. The method used in this study is Structural Equation Modelling with support from Smart PLS software. The Hair method was used to determine the sample size, and the study involved 151 respondents. The results showed that dynamic leadership does not have a direct impact on work productivity, while time management and intellectual intelligence have a direct impact on work productivity. In addition, the ability of intellectual intelligence as a moderator in dynamic management does not affect work productivity and intellectual intelligence as a moderator in time management affects work productivity. The implication is that companies need to improve stronger leadership character and make colleagues understand about good time management so as to increase work productivity both individually and in groups.